2018
DOI: 10.3346/jkms.2018.33.e336
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunity Related to FOXP3+Regulatory T Cells, Th17 Cells and Cytokines in Pediatric Inflammatory Bowel Disease

Abstract: BackgroundWe aimed to investigate mucosal immunity related to forkhead box P3 (FOXP3+) regulatory T (Treg) cells, T helper 17 (Th17) cells and cytokines in pediatric inflammatory bowel disease (IBD).MethodsMucosal tissues from terminal ileum and colon and serum samples were collected from twelve children with IBD and seven control children. Immunohistochemical staining was done using anti-human FOXP3 and anti-RORγt antibodies. Serum levels of cytokines were analyzed using a multiplex assay covering interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…It is reported that IL-4 can induce differentiation of naïve CD4 + T cells into Th2 cells, and Th2 cells secrete IL-9 that acts as a pro-inflammatory factor that affects intestinal mucosal integrity by impairing intestinal barrier function (Bieber et al, 2017). In addition, IL-9 can induce differentiation of cells into Th9 cells in the presence of IL-4, and IL-17 is also a characteristic cytokine of Th17 cells (Cho et al, 2018). TNF-α plays an important role in inflammatory cell activation and epithelial cell permeability.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that IL-4 can induce differentiation of naïve CD4 + T cells into Th2 cells, and Th2 cells secrete IL-9 that acts as a pro-inflammatory factor that affects intestinal mucosal integrity by impairing intestinal barrier function (Bieber et al, 2017). In addition, IL-9 can induce differentiation of cells into Th9 cells in the presence of IL-4, and IL-17 is also a characteristic cytokine of Th17 cells (Cho et al, 2018). TNF-α plays an important role in inflammatory cell activation and epithelial cell permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, Tregs could be considered as therapeutic targets for controlling IBD (Figure 1). Fortunately, many cases of IBD have been successfully cured or alleviated by manipulating Tregs in animal models or patients [45][46][47][48][49][50][51][52][53][54][55][56]. For example, Treg transfer is sufficient to alleviate experimental colitis including IBD, and tTregs and iTregs can work together [57][58][59][60].…”
Section: Tregs Are Associated With the Development Andmentioning
confidence: 99%
“…While the Th17 cells have important implications in autoimmune diseases, the Treg cells control the autoimmune reactivities (2). Mechanically, the frequency of Th17 cells was increased, while that of Treg cells was decreased in the intestinal mucosa of CD patients (3). Previous studies have demonstrated that an imbalance of Th17 and Treg cells is associated with the development of CD (4,5).…”
Section: Introductionmentioning
confidence: 97%